# Calculator search results

Formula
Solve the equation
$1- \dfrac{ -1-a }{ 2 } = \dfrac{ -1+3a }{ 4 }$
$a = 7$
 Solve a solution to $a$
$1 - \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ a } } { 2 } = \dfrac { - 1 + 3 a } { 4 }$
 Organize the expression 
$1 - \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ a } \color{#FF6800}{ - } \color{#FF6800}{ 1 } } { 2 } = \dfrac { - 1 + 3 a } { 4 }$
$1 - \dfrac { - a - 1 } { 2 } = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ a } } { 4 }$
 Organize the expression 
$1 - \dfrac { - a - 1 } { 2 } = \dfrac { \color{#FF6800}{ 3 } \color{#FF6800}{ a } \color{#FF6800}{ - } \color{#FF6800}{ 1 } } { 4 }$
$\color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - a - 1 } { 2 } } = \color{#FF6800}{ \dfrac { 3 a - 1 } { 4 } }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 4 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ - } \color{#FF6800}{ a } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \right ) = \color{#FF6800}{ 3 } \color{#FF6800}{ a } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
$\color{#FF6800}{ 4 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ - } \color{#FF6800}{ a } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \right ) = \color{#FF6800}{ 3 } \color{#FF6800}{ a } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
 Organize the expression 
$\color{#FF6800}{ 2 } \color{#FF6800}{ a } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ a } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$\color{#FF6800}{ 2 } \color{#FF6800}{ a } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ a } = - 1 - 6$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ a } = - 1 - 6$
$- a = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
 Find the sum of the negative numbers 
$- a = \color{#FF6800}{ - } \color{#FF6800}{ 7 }$
$\color{#FF6800}{ - } \color{#FF6800}{ a } = \color{#FF6800}{ - } \color{#FF6800}{ 7 }$
 Change the sign of both sides of the equation 
$\color{#FF6800}{ a } = \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 7 } \right )$
$a = \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 7 \right )$
 Simplify Minus 
$a = 7$
Solution search results